The value of incremental environmental sustainability innovation in the construction industry: an event study. Issue 5 (4th May 2021) - Duong, Linh N. K.; Wang, Jason X.; Wood, Lincoln C.; Reiners, Torsten; Koushan, Mona
Abstract: Investment in the innovation of environmental sustainability in construction has been encouraged due to the industry's resource-intensity. However, it remains unclear how to convince shareholders and construction companies to invest in environmental innovations. This research used the event study method with a sample of 129 announcements in the construction industry from 2011 to 2017 to investigate the relationship between incremental environmental sustainability innovation and the stock market reactions of construction firms. The research finds evidence that the stock market reaction has a strong positive relationship with these announcements. There is also evidence for a relationship between strategic alliance, capital turnover, and the project start date with the stock market reaction. The results provide insight into the benefits of incremental innovations in the construction industry and extend the literature of environmental sustainability innovation by considering contributing factors that affect the relationship between environmental sustainability innovation and firm performance. They provide a useful reference for shareholders to integrate environmental sustainability innovation into their business strategies and allocate their resources more efficiently.